The Influence of Idependent Learning and Independent Campus Program on Students Quality Improvement - Murah, Murah; Mashur, Mashur; Nurhasanah, Nurhasanah; Rahman, Imam Aulia (International Journal of Education, Management, and Technology, 2024)
The implementation of the MBKM (Independent Learning and Independent Campus)program in universities needs to be evaluated so that its impact on students and universities can be known. The purpose of this study was to determine the effect of MBKM (Independent Learning and Independent Campus)on improving the quality of students at Gunung Rinjani University. The research method applied was the causal associative method with a quantitative approach. The population in this study were 273 Gunung Rinjani University students. The research sample was 40 people who participated in the MBKM (Independent Learning and Independent Campus) program with the Purposive sampling technique. The data collection technique used a questionnaire via Google Form and documentation. Data analysis through the stages of classical assumption testing, simple linear regression testing and hypothesis testing with the heled of SPSS. The results of the study obtained a variable regression coefficient of 1.249, which means that the MBKM (Independent Learning and Independent Campus)Program variable has a positive and significant effect on improving the quality of Gunung Rinjani University students. The results of the t-test obtained a significant value for the MBKM (Independent Learning and Independent Campus)Program variable (X) of 0.00, where this value was smaller than the probability value determined by the researcher of 0.05, while the calculated t value obtained was 6.850> from the t-table value of 2.021, so it can be concluded that the MBKM (Independent Learning and Independent Campus)Program variable has a positive and significant effect on improving the quality of students at Gunung Rinjani University.